2022
DOI: 10.1111/jiec.13285
|View full text |Cite
|
Sign up to set email alerts
|

Copper ore material footprints and transfers embodied in domestic and international trade of provinces in China

Abstract: Copper is a critical material for development and plays a profound role in transitioning to a low‐carbon future. China is the main copper consumer in recent decades that has a fast‐growing domestic market accompanied by active international trade. Given the large regional differences within China, it is relevant to understand the domestic driving forces of copper demands and the cascading effects on international regions. Here we combine the newly developed copper ore extraction datasets and the Chinese interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…This could be attributable to the prevalent use of copper in electrical and electronic products, where copper demand is escalating in line with population growth and rising energy needs. Study [49] highlights the potential interplay of population migration on copper's resource dynamics, further affirming our observations. The model returned an R 2 value of 0.7311, a MSE of 0.5702, a MAE of 0.5739, and a RMSE of 0.7551.…”
Section: Model Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This could be attributable to the prevalent use of copper in electrical and electronic products, where copper demand is escalating in line with population growth and rising energy needs. Study [49] highlights the potential interplay of population migration on copper's resource dynamics, further affirming our observations. The model returned an R 2 value of 0.7311, a MSE of 0.5702, a MAE of 0.5739, and a RMSE of 0.7551.…”
Section: Model Resultssupporting
confidence: 81%
“…The remaining sectors, S6 to S42, are subsequently renumbered to sectors S32 to S68. The expanded mathematical expression [49] is as follows: DZ r,s i,j denotes the expanded input-output table, signifying the flow from the first i sector in the r province to the j sector in the s province. Equations ( 5)-( 8) outline the inter-sectoral flows across provinces.…”
Section: Ee-mrio Modelmentioning
confidence: 99%
“…Building on this, we reviewed previous studies and found consistent outcomes (Table S4). One aspect not factored in is the effect of yield: the volume of materials retained in the product during its production.…”
Section: Discussionmentioning
confidence: 65%
“…However, China maintains a substantial reliance on imports for certain strategic resources, such as copper and tin ores, despite possessing the world’s largest reserves of arsenic minerals . China is estimated to have the largest demand for refined copper in Asia, accounting for 50% of the global demand . With regard to the global indirect arsenic trade network, the arsenic demand and consumption center transferred to China during this period, subsequently extending to Southeast Asia.…”
Section: Results and Discussionmentioning
confidence: 99%
“…42 China is estimated to have the largest demand for refined copper in Asia, accounting for 50% of the global demand. 43 With regard to the global indirect arsenic trade network, the arsenic demand and consumption center transferred to China during this period, subsequently extending to Southeast Asia. Trade groups exhibit more regular evolution in recent years, with arsenic trade between countries being less affected by geographical location than in the past and resource-rich countries having significant advantages and forming sporadic trade networks (see Figure S4 of the Supporting Information).…”
Section: Embedded Arsenic Trade Flows Between Countries/regions (Eas ...mentioning
confidence: 99%